ENGLISH WORD “POINT” DERIVATIVE POTENCY AS THE OBJECT OF FUTURE LAND MANAGERS’ LINGUISTIC STUDIES - Yakushko, Kateryna (Sworld-Us Conference proceedings, 2025)
Nowadays it’s important to engage technical students of concrete educational establishments to linguistic studies in order to develop their philological soft skills. Our aim is to represent the experience to find out derivative potency of the word “P